Does the Tunisian Stock Market Overreact? - Fatma Hammami Dhouib; Ezzeddine Abaoub (Asian Academy of Management Journal of Accounting and Finance, 2007)
Research in experimental financial markets suggests that most people tend to overreact to unexpected, striking, and more recent news, and underreact to ordinary or non desirable new events. Many researchers document, as a result that, if one of these behavioral designs exist, then stock prices will follow a mean-reversion phenomenon due to investor's overreaction, and a momentum behavior due to investor's underreaction. This study investigates if such behavior affects stock prices on the Tunisian Stock Market. In other words, we tend to discover the eventual existence of return mean-reversion and/or momentum behavior on the Tunisian Stock Market over the period between January 1997 and December 2005. For this purpose, we have applied a contrarian strategy, which consists of buying the previous (12, 18, 24 and 36 months) loser portfolio and selling the past winner portfolio. Our results point out that, over periods of 18, 24 and 36 months, stock returns exhibit statistically significant mean-reversion phenomenon, while, over 12 months periods, stock returns present significant momentum behavior. This means that stock prices are predictable on the basis of their historical recordings without using any accounting data, in contrast to the weak-form efficient market hypothesis.